Innovative leadership: learning from change management among Malaysian secondary school principals - Othman, Azam; Abd Rahman, Hamidon (IDOSI Publication, 2013)
This paper explores the secondary school Principals views and experiences in managing change their organizations. The focus is upon how innovative the Principals are in their decision-making and leadership styles. The study adopts a qualitative research methodology using open-ended interviews to explore the leadership styles of the six Principals in selected secondary schools in Malaysia. The analysis of the data revealed most of the Principals did not realise that they were being innovative because they had been using the innovative strategies simply thinking they were finding a solution to their problems. Another common perception among the Principals was that being innovative only involves computers and technology. This idea resonated throughout the interviews. The interview transcriptions also revealed that Principals have positive perceptions about the changes that have been happening in the Malaysian education system. Other emergent themes included: Principals as catalysts for change; staffs’ trust towards Principals; Principals’ confidence in solving problems; Principals’ boldness in discovering solutions and the importance of a people-centred approach for leadership. The participants of the study comprised six secondary school Principals who were all recipients of the Innovative Leader’s Award from the Malaysian Ministry of Education. The study also investigated the thinking processes for leaders’ innovation as well as their attitudes towards their subordinates.